2022
DOI: 10.1177/20406223221084833
|View full text |Cite
|
Sign up to set email alerts
|

Associations between age-related hearing loss, cognitive decline, and depression in Chinese centenarians and oldest-old adults

Abstract: Objective: Age-related hearing loss (ARHL) and age-related cognitive decline (ARCD) are leading causes of disability in older adults. ARHL may increase ARCD risk and cause depression development. This study aimed to explore the associations of ARHL with ARCD and depression in Chinese centenarians and oldest-old adults. Methods: A household survey was conducted on 859 centenarians and oldest-old adults residing in 16 cities and counties in China. Basic information was collected using interview questionnaires, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…First of all, with the increase of age, people’s physical functions continue to decline, and they are more likely to suffer from various diseases, such as hypercortisolemia, hypertension and diabetes ( Brown et al, 2004 ), as well as injuries and even physical disabilities. In addition, muscle strength tends to weaken and hearing loss occurs with age, and previous studies have linked muscle weakness and age-related hearing loss to depressive disorders ( Chen et al, 2020 ; Feng et al, 2022 ). Besides, some drugs used to treat diseases of the elderly may have side effects and increase the risk of depressive disorders ( Beers and Passman, 1990 ; You et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, with the increase of age, people’s physical functions continue to decline, and they are more likely to suffer from various diseases, such as hypercortisolemia, hypertension and diabetes ( Brown et al, 2004 ), as well as injuries and even physical disabilities. In addition, muscle strength tends to weaken and hearing loss occurs with age, and previous studies have linked muscle weakness and age-related hearing loss to depressive disorders ( Chen et al, 2020 ; Feng et al, 2022 ). Besides, some drugs used to treat diseases of the elderly may have side effects and increase the risk of depressive disorders ( Beers and Passman, 1990 ; You et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar studies have also shown that c-Abl blocker imatinib can significantly reduce plasma Aβ protein levels [77]. Intraperitoneal injection of the drug into AD model mice can not only ameliorate cognitive decline but also reduce neuronal apoptosis and Tau protein phosphorylation [78]. In addition, a study on AD-related diseases in humans showed that the level of c-Abl in the brains of AD patients was obviously higher than that in the brains of controls.…”
Section: Roles Of C-abl Blockersmentioning
confidence: 94%
“…Education is a significant demographic factor influencing MMSE 41 . The optimal cut‐off points for defining cognitive impairment were determined based on education levels and established based on previous literatures 42–44 . In these literatures, MMSE was proved to be feasible among Chinese for cognitive impairment screening.…”
Section: Methodsmentioning
confidence: 99%
“…In these literatures, MMSE was proved to be feasible among Chinese for cognitive impairment screening. Cognitive impairment was defined as: MMSE ≤ 17 for illiteracy; MMSE ≤ 20 for primary school (1–6 years of education), and MMSE ≤ 24 for middle or higher school (more than 6 years of education) 42–44 …”
Section: Methodsmentioning
confidence: 99%